The L1 retrotransposition assay: A retrospective and toolkit - Rangwala, Sanjida H.; Kazazian, Haig H. (Methods (San Diego, Calif.), 2009)
LINE1s (L1s) are a class of mammalian non-LTR (long terminal repeat) retroelements that make up nearly 20% of the human genome. Because of the difficulty of studying the mobilization of endogenous L1s, an exogenous cell culture retrotransposition assay has become integral to research in L1 biology. This assay has allowed for investigation of the mechanism and consequences of mobilization of this retroelement, both in cell lines and in whole animal models. In this paper, we outline the genesis of in vitro retrotransposition systems which led to the development of the L1 retrotransposition assay in the mid-1990s. We then provide a retrospective, describing the many uses and variations of this assay, ending with caveats and predictions for future developments. Finally, we provide detailed protocols on the application of the retrotransposition assay, including lists of constructs available in the L1 research community and cell lines in which this assay has been applied.